Paura, terrore ed esplosione. “... l’importanza del fuoco e la costruzione di bombe...” - Bojanić, Petar (Filosofia, 2017)
The present paper analyzes the question of terrorism through the conceptual lenses of the bomb and the explosion; more specifically, through an investigation of such authors as Augustine, Roger Bacon, Francis Bacon, Hobbes, Fichte, and Hegel, it shows the inextricable nexus between terror, fear, and sovereign power. The paper argues that terror and sovereignty are strictly linked to one another through a metaphysical dialectics between Unity and Multiplicity, which is replaced by the bomb itself. The paper concludes with the argument that the current response to terror and its explosions amounts to what he calls a therrorethical response.